Electro‐Photoluminescence Color Change for Deformable Visual Encryption. Issue 22 (21st April 2020) - Lee, Gilwoon; Kong, Minsik; Park, Doowon; Park, Junho; Jeong, Unyong
Abstract: Although structural coloring and photoluminescence (PL) have been investigated for radiation‐responsive color change, electroluminescence (EL) has not been used for the radiation‐responsive system. An electro‐photoluminescence (EPL) color change is presented here. The phosphors in the alternating current electroluminescence (ACEL) act simultaneously as electro‐luminophores and photo‐luminophores. The EPL chromaticity is systematically investigated depending on the ACEL frequency and UV intensity. It is found that the PL variation depending on UV intensity is the mechanism of the EPL color change. It is revealed that EL and PL can be controlled independently in the low electric field so that the EPL chromaticity can be adjusted by a linear combination of the EL color and the PL color. The EPL color‐changing device is used as a deformable visual encryption system and a soft skin for a soft robotic rover, imitating the concealment and signaling functions in nature. Abstract : An electro‐photoluminescence (EPL) color‐change system is presented. The chromaticity of EPL can be controlled systematically in a wide range of color variation while maintaining high luminance. The EPL color‐changing device can be used in a deformable visual encryption and as a soft skin for a soft robotic rover.